Bacterial infection and implant ioosening in hip and knee Aathroplasty: evaluation of 209 cases - Dapunt, Ulrike A.; Radzuweit-Mihaljevic, Stephanie; Lehner, Burkhard; Hänsch, Gertrud Maria; Ewerbeck, Volker (Materials, 2016)
The aim of this study was to evaluate bacteria species detected in a large number of patients treated for prosthetic joint infection of the hip and knee at a single specialized center. Furthermore, the rate of implant loosening was investigated in a time-dependent manner for the most frequently detected bacteria species. A retrospective analysis of patients (n = 209) treated for prosthetic joint infection of the hip and knee was performed. The following parameters were evaluated: C-Reactive Protein (CRP) concentration, microbiological evaluation of tissue samples, loosening of the implant, the time that had elapsed since the primary prosthetic joint replacement, and the duration since the last surgical intervention. Coagulase-negative Staphylococcus spp. were most frequently detected, followed by Staphylococcus aureus. Differences in CRP concentration were detected among various bacteria species. Osteolysis was not associated with one causative agent in particular. Patients who had undergone previous revision surgery had a higher probability of implant loosening. Coagulase-negative Staphylococcus spp. are the most common causative agents of prosthetic joint infection and show no significant differences with regard to implant loosening or the time-course when compared to S. aureus. Infections with Enterococcus spp. seem to develop faster than with other bacteria species. The risk of implant loosening increases with revision surgery, in particular in the hip joint.